Future trends in materials manufacturing for low carbon building stocks: A prospective macro-scale analysis at the provincial level. (1st January 2023) - Alaux, Nicolas; Ruschi Mendes Saade, Marcella; Hoxha, Endrit; Truger, Barbara; Passer, Alexander
Abstract: In order to reduce the greenhouse gas (GHG) emissions of buildings, the literature has investigated many strategies to tackle operational emissions, which are traditionally the largest contributor to overall emissions. As a result, embodied emissions are gaining increased attention, not only due to the decrease in the relative share of operational emissions but also due to increased material needs, e.g. the use of additional thermal insulation in buildings. Some of these strategies, such as the decarbonisation of the energy grid, could also help decrease the embodied emissions of building materials. The objective of this paper is to investigate the influence of increased renewable electricity use in building material production. It also examines future trends in the manufacturing processes – such as an intensified use of bioenergy, improvements in energy efficiency and the introduction of carbon capture and storage – on the GHG emissions of buildings. These strategies are analysed in a combined "future materials" scenario on a macro scale within the Tyrol province in Austria. With a focus on new residential constructions, six design variations of two building case studies are assessed using life cycle assessment. They are then projected to 2050 at the provincial level. The results of the future materials scenario point towards a promising embodied GHG reduction, up to 19% in this analysis. Larger mitigation effects would appear in the 2040s and 2050s, meaning future manufacturing technologies can be seen as a long-term investment. Their reduction potential surpasses the potential impact of an increase in wooden constructions. The latter achieved up to 7% reduction in GHG emissions, which would be mostly visible in the early decades rather than in later ones. These reduction percentages remain lower than those which could be attained at the operational energy level, with reductions of up to 72%. The obtained results are discussed in the light of other published regional and global studies to identify the possible sources of variations. Critical reflections on carbon capture and storage, as well as renewables, additionally highlight the intrinsic challenges of such key technologies. Graphical abstract: Image 1 Highlights: Analysis of future trends in manufacturing process (renewable electricity, etc.) Projection at the building stock level using life cycle assessment. Comparison with impact of renewable electricity on the operational stage. 19% reduction achieved (embodied emissions) versus 72% (operational emissions). Reflections on other studies and key technologies (carbon capture and storage).